Estimation of Variance Components Using a Step-by-Step Approach - Aydin, Cuneyt (ASCE-AMER SOC CIVIL ENGINEERS, 2011)
We may obtain a unique parameter vector solution from a combination of individually estimated parameter vectors by adjusting different observation groups. This kind of combination method, the so-called step-by-step procedure, is widely used in geodesy. We derive Helmert-type variance-component estimates for several observation groups via this step-by-step approach. In the estimation step, only individual results are used; hence, this procedure is called step-by-step estimation of variance components. The novel approach is applied to a horizontal control network and a leveling network. DOI: 10.1061/(ASCE)SU.1943-5428.0000043. (C) 2011 American Society of Civil Engineers.
Keywords: Variance analysis; Parameters; Leveling; Surveys; Variance components; Step-by-step method; Helmert-type estimates; ROBUST ESTIMATION; Engineering